Bibliometric Analysis Commind Relax Support on Anxiety Among Pre Operative Patients - Farenzi Budi Setiaprabhawa; Satriya Pranata; Amin Samiasih (Babali Nursing Research, 2023)
Background: Intervention in the management of anxiety is an approach that is currently being developed by researchers in various countries. This research needs the latest information and trends for future research topics related to cognitive behavior therapy interventions, mindfulness, relax, and support for anxiety in preoperative patients.